MEDICINAL PLANTS SOLD IN THE MARKET ADOLPHO LISBON IN THE MUNICIPALITY OF MANAUS/AM - Linduina Mendes Maia, Maria (Journal of Interdisciplinary Debates, 2022)
The custom of using plants for medicinal purposes is widespread throughout the world. In the Amazon region, markets and fairs play leading roles when it comes to marketing medicinal plants. This work aimed to: identify part of the diversity of medicinal plants sold in the Municipal Market Adolfo Lisboa, in the Municipality of Manaus/AM. As methodological procedures, the following strategies were used: participant observation, simplified questionnaire to local traders in order to identify the medicinal plants sold in the Adolpho Lisboa market. Result: Of the 23 plants commercialized at Mercado Adolpho Lisboa with the purpose of medicinal use obtained during the research, the families with the highest representation identified were: Lamiaceae, followed by Malvaceae, Asteraceae and Fabaceae. The plants are usually obtained from markets, street fairs in neighborhoods or home gardens. Conclusion: Thus, it is concluded that the population has extensive knowledge of medicinal plants and uses them constantly believing in their healing power, and these are marketed fresh in bundles (leaves, branches and also the whole plant as a seedling), dehydrated (dried leaves, bark, seeds, nuts) and packaged (oils), through herb traders at the Adolpho Lisboa municipal market.